Growth factors in development - Birchmeier-Kohler, Carmen (Current topics in developmental biology, 2011)
This new volume of the renowned serial Current Topics in Developmental Biology covers the important features of growth factors in development. With an international board of authors, this volume will be invaluable for researchers in cell, developmental and molecular biology. Provides researchers an overview and synthesis of the latest research findings and contemporary thought in the area This volume provides an up-to-date and timely perspective